A Mixed-Signal Programmable Time-Division Power-On-Reset and Volume Control Circuit for High-Resolution Hearing-Aid SoC Application. (18th April 2018) - Chen, Chengying; Chen, Liming; Yang, Jun
Abstract : A mixed-signal programmable Time-Division Power-On-Reset (TD-POR) circuit based on 8-bit Successive Approximation Analog-to-Digital Converter (SAR ADC) for accurate control in low-power hearing-aid System on Chip (SoC) is presented in this paper. The end-of-converter (EOC) signal of SAR ADC is used as the mode-change signal so that the circuit can detect the battery voltage and volume voltage alternately. And the TD-POR circuit also has brown-out reset (BOR) detection capability. Through digital logic circuit, the POR, BOR threshold, and delay time can be adjusted according to the system requirement. The circuit is implemented in SMIC 0.13  μ m 1P8M CMOS process. The measurement results show that, in 1 V power supply, the POR, BOR, and volume control function are accomplished. The detection resolution is the best among previous work. With 120 Hz input signal and 15 kHz clock, the ADC shows that Signal to Noise plus Distortion Ratio (SNDR) is 46.5 dB and Effective Number Of Bits (ENOB) is 7.43 bits. Total circuit power consumption is only 86  μ w for low-power application.